Analysis of biometric parameters of 2340 eyes measured with optical biometer Lenstar LS900 in a Caucasian population. Issue 1 (January 2022) - Popov, Ivajlo; Waczulikova, Iveta; Stefanickova, Jana; Valaskova, Jela; Tomcikova, Dana; Shiwani, Haaris A.; Delev, Delian; Rodrigo, Luis; Saxena, Sandeep; Kruzliak, Peter; Krasnik, Vladimir
Objectives: To describe the pattern and mutual relationships between basic biometric characteristics of the eye in a Central European Caucasian population. Methods: A single-centre retrospective study of 2340 patients (965 males, 1375 females) scheduled for cataract surgery between 2014 and 2016. Measurements using laser interferometry included AL (axial length), K (average corneal curvature), ACD (anterior chamber depth), LT (lens thickness), CCT (central corneal thickness), AST (astigmatism) and WTW (white to white). Subjects were stratified by gender and controlled for age. Descriptive, correlation and regression analyses were performed on the data. Results: The mean AL was 23.33 ± 1.01 mm – higher in males (23.59 ± 0.99 mm), in comparison to females (23.15 ± 0.99 mm). The elderly had lower ACD and higher LT, while males had higher AL independent of age. Furthermore, LT and K decreased with AL, while ACD decreased with LT and increased with AL independent of age and gender. Conclusions: The estimates of the biometrics are obtained on a large sample of subjects and can serve as normative values for Lenstar LS900 in the Central European Caucasian population.